APPLICATION OF ISO 45001:2018 STANDARD ON CONVEYOR BELT MACHINE OPERATIONS AT PT CEMINDO GEMILANG - Pahrudin, Iip; Supriyatna, Deddy; Sumitra, Sumitra (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Negeri Semarang, 2023)
K3 management in an industry or company becomes a contrast when problems in this domain occur. Because K3 is an element that involves humanity, law, politics and economics. With many important aspects involved, of course the responsibility in carrying out the task of managing K3 is very important. The research was conducted at PT Cemindo Gemilang , Banten with a research focus on conveyor belt machine operations. Data collection was carried out by direct observation with a type of experimental descriptive research. The points that will be discussed in this research are ISO 4500:2018 points in clause 3.21 occupational health and safety risks, K3 risks, 8.2 emergency preparedness and response, and 9.1 monitoring, measuring, analyzing and evaluating work. The research results show that PT Cemindo Gemilang has fulfilled the criteria for implementing ISO 4500:2018, ISO 4500:2018 points in clause 3.21 occupational health and safety risks, K3 risks, 8.2 emergency preparedness and response, and 9.1 monitoring, measurement, analysis and evaluation Work. With the